MORTALITY AND CAUSE OF DEATH IN ABUTH, ZARIA: 1999 – 2005 - Dahiru, T. (Association of Resident Doctors (ARD), University College Hospital, Ibadan, 2010)
BACKGROUND: Accurate mortality statistics are needed for policy formulation, implementation and monitoring of health intervention that are aimed at improving the health status of the people. Mortality level is one of the indicators of the quality of life and status of health of a population. However, accurate collection, collation, analysis and interpretation of such data is poorly organised in developing nations, including Nigeria leading to a gap in health policy formulation, implementation and monitoring. Therefore, policies and strategies for disease prevention are based on empirical evidence rather than on data primarily collected to formulate disease specific interventions. Though, hospital data have inherent deficiency in its use to design prevention. However, when accurately generated and adequately managed would provide both qualitative and quantitative information on morbidity and mortality if not for the entire society at least for a segment of the population utilizing it. We implemented a system of death certification to determine causes and pattern of mortality in Ahmadu Bello University Teaching Hospital, Zaria METHODS: From May 1999 to November 2005, all case folders of deceased patients were retrieved from the central library of health information management department of the hospital; case folders of deceased patients are required to have in them a completed IFMCCD (International Form of Medical Certification of Cause of Death). All case folders of deceased patients after relevant information were extracted by the staff of health management information department, were passed on to the staff of department of Community Medicine directly involved in this study. The completed cause of death certificates received in the department of Community Medicine (between May 1999 and November 2005), were examined. Coding rules were employed to select the appropriate code for those certificates that were incorrectly completed. The underlying cause of death as identified from the correctly completed IFMCCDS is coded according to ICD-10. RESULTS: For the period under study, there were 4019 deaths: 2212 males and 1807 females. Total of 2914 (72.5%) deaths were certified, using the IFMCCD of which 1641 of them were males and 1273 females and formed the basis of this analysis. Coverage rates ranges from 56.2% in 2001 to 85% in 1999. The proportion of garbage codes ranges from 0% to 2.4% while the three leading causes of death are HIV infection, road traffic accident (RTA), and cardiovascular diseases among the ten. The time-trend of the leading causes of death show RTA maintaining steady upward climb while malaria, septicemia, PEM, sepsis in the neonatal period shows unsteady fluctuation. CONCLUSION: This study assessed the pattern of mortality and causes of death in ABU Teaching Hospital, Zaria; it also provided information on leading causes of death.